PENGARUH KECERDASAN FINANSIAL TERHADAP MOTIVASI KERJA TUKANG PARKIR WILAYAH SUKAJADI PEKANBARU - Hanna Karina Hutabarat; Daeng Ayub Natuna; Dafetta Fitrilinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The formulation of the research problem is how high is the opportunity for parking attendants' financial intelligence in the Sukajadi Region of Pekanbaru, how high is the job motivation of a parking attendant in the Sukajadi area of Pekanbaru, is there any influence of financial intelligence on the work motivation of a parking attendant in the Sukajadi area of Pekanbaru. The purpose of this study was to determine the level of financial intelligence of parking attendants in the Sukajadi area of Pekanbaru, to determine the level of work motivation of parking attendants in the Sukajadi area of Pekanbaru, to determine whether there was an influence of financial intelligence on the work motivation of the parking attendants in the Sukajadi area of Pekanbaru. This type of research is ex-post facto, which is a type of research in which the independent variable is an event that has occurred, with a quantitative approach. The population in this study is the parking attendant for the Suakajadi area of Pekanbaru as many as 60 members. The sampling technique using Simple Random Sampling is a method of drawing from a population or universe in a certain way so that each member of the population or universe has the same opportunity to be selected or taken. There is a significant influence between financial intelligence (X) variables on work motivation (Y) Parking attendants in Sukajadi Pekanbaru area, which has a large effect of 35.20% with a low interpretation, because there is still 64.8% determined by other factors that are not be a part of this research. This effect is illustrated by every one unit increase in financial intelligence (X) followed by an increase in work motivation (Y) of 0.88 one unit.Key Words: Financial Intelligence, Work Motivation, Parking Lot